Adolescent Mental Health: An Emerging Public Health Concern - Sharma, Poojan (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Adolescence is the phase of life between childhood and adulthood, from ages 10 to 19. They experience rapid physical, cognitive and psychosocial growth. Adolescent covers one sixth of the global population. An estimated 1.1 million adolescents die each year. The leading causes are road traffic injuries, suicide and interpersonal violence.